The role of natural products in modern drug discovery. - CALIXTO,JOÃO B. (2019)
Abstract: The global medicine market is about 1.1 trillion US dollars. About 35 percent of medicines have originated from natural products. Brazil presents the largest biodiversity in the world, with more than 50,000 species of higher plants. However, few innovative products have been developed in Brazil from active constituents derived from the Brazilian biodiversity. Scientific evidences on plants and venoms have been internationally published by Brazilian scientists over the last 4 decades; but few examples of innovative products are commercially available. Few examples include the anti-hypertensive drug captopril first identified in the venom of the Brazilian viper Bothrops jararaca by Professor Sergio Ferreira; and some phytotherapeutic agents such as Acheflan®, Syntocalmy® and Melagrião® produced by standardized plant extracts with scientific proof of safety, efficacy and quality. Still, only Acheflan® and Melagrião® are obtained from native Brazilian plants. Several issues contribute to the lack of innovative products from the Brazilian biodiversity, but in my opinion, the most challenging ones are i) the lack of specific regulations to allow researchers and companies to access biodiversity for the purposes of scientific and technological innovation; and ii) the absence of a long-term government program to support research and innovation in this field.